Phenol conjugation in the desert hopping mouse, notomys alexis - Ramli , Johari; Wheldrake , J. F. (Elsevier, 1978)
1. The ratio of phenyl sulphate to phenyl glucuronide formed in vitro follows that seen in whole animals. 2. Phenyl sulphate formation from phenol, ATP and sulphate is subject to inhibition by phenol at high concentrations. 3. Addition of exogenous PAPS stimulates phenyl sulphate formation. It is concluded that availability of PAPS limits the rate of phenyl sulphate formation. 4. The preferential formation of phenyl sulphate at low phenol concentrations is explicable by the observation that the sulphotransferase has a higher affinity for phenol than does the UDP-glucuronyl-transferase.